2015
DOI: 10.1177/0954406215612816
|View full text |Cite
|
Sign up to set email alerts
|

Variability analysis of vibrational responses in a passenger car considering the uncertainties of elastomers

Abstract: Passenger cars have many elastomeric joints that are used to reduce the vibration transmission from the source to the cabin structure. In the design stage, the dynamic characteristics of the elastomeric joints are optimally determined in order to satisfy the design goals for interior noise and vibration. However, the material properties of the elastomeric joints have large variations due to production variability. In addition, operational conditions, e.g. environmental temperature, vary according to the locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Among them, thermo-oxidative aging is a dominant factor in the degradation of mechanical properties in elastomers. The dynamic characteristics of elastomers are also heavily dependent upon frequency and operational temperature (Jung et al 2011;Kwon and Lee 2015;Lee and Hwang 2011;Lee et al 2016). In this paper, a variability analysis procedure for the thermal oxidative aging for elastomers is described.…”
Section: Electronic Submissionmentioning
confidence: 99%
“…Among them, thermo-oxidative aging is a dominant factor in the degradation of mechanical properties in elastomers. The dynamic characteristics of elastomers are also heavily dependent upon frequency and operational temperature (Jung et al 2011;Kwon and Lee 2015;Lee and Hwang 2011;Lee et al 2016). In this paper, a variability analysis procedure for the thermal oxidative aging for elastomers is described.…”
Section: Electronic Submissionmentioning
confidence: 99%
“…For example, Resh 14 investigated the uncertainty in the dynamic properties of engine mounts while Donders et al 15 used a Monte Carlo simulation to study the variation in the natural frequencies of an automotive vehicle body-in-white arising from the uncertainty in the spot welds 1 characteristics. The variability in the natural frequencies of a car windscreen due to temperature is studied by Scigliano et al 16 More recently, Kwon and Lee 17 modelled the uncertainty in the elastomeric joints and used the eigenvector dimension reduction method in order to obtain the variability in the dynamic response of the vehicle. They showed that the acceleration on the seat track can vary up to 6 dB due to the uncertainty in the sub-frame elastomer mounts.…”
Section: Introductionmentioning
confidence: 99%
“…The variability in the natural frequencies of a car windscreen due to temperature is studied by Scigliano et al. 16 More recently, Kwon and Lee 17 modelled the uncertainty in the elastomeric joints and used the eigenvector dimension reduction method in order to obtain the variability in the dynamic response of the vehicle. They showed that the acceleration on the seat track can vary up to 6 dB due to the uncertainty in the sub-frame elastomer mounts.…”
Section: Introductionmentioning
confidence: 99%